UTERINE HORN LIPOMA WITH CONCURRENT PYOMETRA IN AN INTACT DACHSHUND BITCH - JOSEPH, CECILIA; GEORGE, RAVI SUNDAR; SRIDEVl, P; RANGASAMY, S; JEMIMAH, RACHEL (The Indian Journal of Animal Reproduction, 2015)
Uterine horn lipoma with concurrent pyometra in an intact Dachshund bitch, its diagnosis and surgical management is reported.